2008
DOI: 10.1002/bsl.798
|View full text |Cite
|
Sign up to set email alerts
|

Neurophilosophical perspectives of neuroimaging in forensic psychiatry—giving way to a paradigm shift?

Abstract: Forensic psychiatry is concerned with the relationship between psychiatric abnormalities and legal violations and crimes. Due to the lack of available biological criteria, evaluation and therapy in forensic psychiatry have so far been restricted to psychosocial and mental criteria of offenders' personalities. Recent advances in neurosciences allow a closer approach to the neural correlates of personality, moral judgments and decision-making. We propose to discuss the introduction of biological criteria in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Despite the non-influence of neuroimagery, however, jurors who were not provided with a neuroimage indicated that they believed neuroimagery would have been the most helpful kind of evidence in their evaluations of the defendant. Fueled by advances in magnetic resonance imaging (MRI), functional MRI (fMRI), and other imaging technology, neuroscience evidence -particularly neuroimage-based evidence -has started to find its way into trials of criminal cases, offered to help resolve a range of issues, among them competence, capacity to form a mental state necessary to be guilty of a crime, criminal responsibility (insanity), as mitigation evidence in capital murder penalty phase hearings (Appelbaum, 2009;Baskin, Edersheim, & Price, 2007;Erickson, 2010;Fabian, 2010;Fiegenson, 2006;Greely, 2008;Hughes, 2010;Jones Buckholtz, Schall, & Marois, 2009;Mobbs, Lau, Jones, & Frith, 2007;Moriarty, 2008;Sinnott-Armstrong, Roskies, Brown, & Murphy, 2008;Vincent, 2011;Witzel et al, 2008). In anticipating this development in neuropsychiatric expert testimony, numerous commentators -from both the legal and scientific communities -have cautioned about a range of inadequacies in the current state of the art and science, especially if offered in legal settings.…”
mentioning
confidence: 99%
“…Despite the non-influence of neuroimagery, however, jurors who were not provided with a neuroimage indicated that they believed neuroimagery would have been the most helpful kind of evidence in their evaluations of the defendant. Fueled by advances in magnetic resonance imaging (MRI), functional MRI (fMRI), and other imaging technology, neuroscience evidence -particularly neuroimage-based evidence -has started to find its way into trials of criminal cases, offered to help resolve a range of issues, among them competence, capacity to form a mental state necessary to be guilty of a crime, criminal responsibility (insanity), as mitigation evidence in capital murder penalty phase hearings (Appelbaum, 2009;Baskin, Edersheim, & Price, 2007;Erickson, 2010;Fabian, 2010;Fiegenson, 2006;Greely, 2008;Hughes, 2010;Jones Buckholtz, Schall, & Marois, 2009;Mobbs, Lau, Jones, & Frith, 2007;Moriarty, 2008;Sinnott-Armstrong, Roskies, Brown, & Murphy, 2008;Vincent, 2011;Witzel et al, 2008). In anticipating this development in neuropsychiatric expert testimony, numerous commentators -from both the legal and scientific communities -have cautioned about a range of inadequacies in the current state of the art and science, especially if offered in legal settings.…”
mentioning
confidence: 99%
“…Kulynych () argues that neuroscientific findings are not specific enough to inform questions of volitional and cognitive impairment, and that there are no objective criteria by which to quantify the extent of brain damage. Despite these concerns, however, a contingent of commentators have argued recently that increasingly sophisticated neurobiological techniques do allow scientists to address the biological basis of behaviors (Muller et al, ) and that neuroscience is now advanced enough to contribute to forensic psychiatry (Witzel, Walter, Bogerts, & Northoff, ).…”
mentioning
confidence: 99%
“…The importance of promptly and continuously administered antipsychotic substances is beyond any controversy in order to cope adequately with acute schizophrenic symptoms so as to prevent relapse, which is more likely to occur in the absence of neuroleptic treatment (Kane, 1982). Special emphasis should be given to neurobiological alterations of prisoners' brains as well (Witzel, Walter, Bogerts, & Northoff, 2008) as advanced technical diagnostic methods usually are rarely applied to prisoners.…”
Section: Mean9sdmentioning
confidence: 99%